THE EFFECT OF USING PROBLEM-BASED LEARNING (PBL) METHOD ON SPEAKING ABILITY OF THE FIRST YEAR EXACT SCIENCE STUDENTS OF SMAN 8 PEKANBARU - Khairunnisha Effendi; Fakhri Ras; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research was aimed to investigate whether problem-based learning (PBL) method can affect students’ speaking ability. The research was conducted at the first year exact science students of SMA Negeri 8 Pekanbaru. The number of the students was 324 in 9 classes. Due to the large population, the cluster random sampling was used to determine the sample, then lottery taking is applied with the result that X MIPA 7 and X MIPA 8 were selected. In conducting the research, a quasi-experimental method was applied in which X MIPA 7 as the experimental class and X MIPA 8 as the control class. There were 72 students as the sample of this research. This research design used one group pre-test post-test. Experimental class was taught by using PBL method and control class was taught by using conventional method. The pre-test at the beginning and the post test at the end of the treatment were administered. The collected data were analyzed by using independent sample t-test. From the calculation, it was found that Sig. (2-tailed) was 0.000 < 0.05. Since Sig. (2-tailed) was lower than α = 0.05, Hi was accepted. It means that there is significant effect in using problem-based learning (PBL) method on students’ speaking ability. The implication of the findings was the control group should be enhanced by the similar method to increase their speaking ability.Key Words: Speaking, Speaking Ability, Problem-Based Learning (PBL) Method